A Queer Little History of Art. - Pilcher, Alex (Londen : Tate Publishing, 2017)
Schiele, Egon ; Grant, Duncan ; Höch, Hannah ; Hockney, David ; Ligon, Glenn; Muholi, Zanele ; Mitchell, Allyson ; Kashiki, Tomoko
boek